Anti-SARS-CoV-2 Immunoglobulin Isotypes, and Neutralization Activity Against Viral Variants, According to BNT162b2-Vaccination and Infection History - Tarkowski, Maciej; de Jager, Wilco; Schiuma, Marco; Covizzi, Alice; Lai, Alessia; Gabrieli, Arianna; Corbellino, Mario; Bergna, Annalisa; Ventura, Carla Della; Galli, Massimo; Riva, Agostino; Antinori, Spinello (Frontiers in Immunology, 2021)
Purpose To compare SARS-CoV-2 antigen-specific antibody production and plasma neutralizing capacity against B.1 wild-type-like strain, and Gamma/P.1 and Delta/B.1.617.2 variants-of-concern, in subjects with different Covid-19 disease and vaccination histories. Methods Adult subjects were: 1) Unvaccinated/hospitalized for Covid-19; 2) Covid-19-recovered followed by one BNT162b2 vaccine dose; and 3) Covid-19-naïve/2-dose BNT162b2 vaccinated. Multiplex Luminex® immunoassays measured IgG, IgA, and IgM plasma levels against SARS-CoV-2 receptor-binding domain (RBD), spike-1 (S), and nucleocapsid proteins. Neutralizing activity was determined in Vero E6 cytopathic assays. Results Maximum anti-RBD IgG levels were similar in Covid-19‑recovered individuals 8‒10 days after single-dose vaccination and in Covid-19-naïve subjects 7 days after 2nd vaccine dosing; both groups had ≈2‑fold higher anti-RBD IgG levels than Unvaccinated/Covid-19 subjects tracked through 2 weeks post-symptom onset. Anti-S IgG expression patterns were similar to RBD within each group, but with lower signal strengths. Viral antigen-specific IgA and IgM levels were more variable than IgG patterns. Anti-nucleocapsid immunoglobulins were not detected in Covid-19-naïve subjects. Neutralizing activity against the B.1 strain, and Gamma/P.1 and Delta/B.1.617.2 variants, was highest in Covid‑19-recovered/single-dose vaccinated subjects; although neutralization against the Delta variant in this group was only 26% compared to B.1 neutralization, absolute anti-Delta titers suggested maintained protection. Neutralizing titers against the Gamma and Delta variants were 33‒77% and 26‒67%, respectively, versus neutralization against the B.1 strain (100%) in the three groups. Conclusion These findings support SARS-CoV-2 mRNA vaccine usefulness regardless of Covid-19 history, and confirm remarkable protection provided by a single vaccine dose in people who have recovered from Covid-19.